Perlindungan Hukum terhadap Perempuan sebagai Korban Tindak Pidana Kekerasan dalam Rumah Tangga Berdasarkan UU No. 23 Tahun 2004 - Holifia Holifia; Fathorrahman Fathorrahman (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
Crimes that occur in human life include social events that will always be faced by every human being, society and even the State. Crimes can only be prevented and reduced but it is impossible to completely eliminate them. One of these crimes is violence. This study aims to determine the form of legal protection that has been carried out by the government, law enforcement officers and parties who have the right to provide protection for women as victims of domestic violence and to determine the obstacles faced by law enforcement in providing protection for women as victims of domestic violence. The results of the study indicate that the role of law enforcement officers in protecting women's rights has begun since the discovery of cases of violence by police officers until the time of examination in court and in efforts to provide legal protection for women who are victims of domestic violence, several obstacles were found. These obstacles include factors of the victim themselves, factors of law enforcement officers, factors of facilities and infrastructure, community factors, cultural factors.